A cache of jewels and other collective nouns - Heller, Ruth 1924- (New York Scholastic, 1989)
Rhyming text and illustrations introduce a variety of collective nouns such as a "drift of swans" and a "clutch of eggs."
Keywords: English language -- Collective nouns -- Juvenile literature; English language -- Terms and phrases -- Juvenile literature